(untitled) (Bangladesh Journal of Pharmacology, 2015)
Ten fungal strains isolated from Edgeworthia chrysantha, one of traditional medicinal plants in China, were evaluated their antimicrobial activities against three human pathogens, Escherichia coli, Staphyloccocus aureus and Candida albicans, and two phytopathogens, Rhizoctonia cerealis and Colletotrichum gloeosporioides. The results indicated that most ethyl acetate extracts of fermentation broth of these fungal endophytes had stronger antimicrobial activities than their fermentation broth. Among these endophytic strains, both fermentation broth and the ethyl acetate extract of strain D showed the strongest inhibitory effects on all pathogens. Strains 5-19 and BZ also exhibited potent antibacterial activities. However, other strains had weak or no antimicrobial effect. This was the first report on the isolation and antimicrobial effects of endophytic fungi from E. chrysantha.